Making an Edition in an App. Issue 1 (9th November 2021) - Bordalejo, Barbara; Gibbings, Lina; North, Richard; Robinson, Peter
Abstract : The massive increase in the use of mobile devices over the last years, with over half of all accesses to the internet now coming from mobile devices, presents a challenge and an opportunity to textual scholars. It has long been suggested that digital technologies may help scholarly editors find new audiences for their work: work which has traditionally lain on library shelves with only the occasional visitor. In this paper we describe an attempt to plan, make and distribute an edition – the CantApp, presenting in its first iteration the General Prologue of Geoffrey Chaucer's Canterbury Tales – designed specifically for mobile device use. We reflect on the difficulties we faced, the initial reception of the app, and draw conclusions which might be useful for other scholarly projects.